CatbNet: A Multi Network Analyzer for Comparing and Analyzing the Topology of Biological Networks - Pournoor, Ehsan (Curr Genomics, 2019)
BACKGROUND: Complexity and dynamicity of biological events is a reason to use comprehen-sive and holistic approaches to deal with their difficulty. Currently with advances in omics data genera-tion, network-based approaches are used frequently in different areas of computational biology and bio-informatics to solve problems in a systematic way. Also, there are many applications and tools for net-work data analysis and manipulation which their goal is to facilitate the way of improving our under-standings of inter/intra cellular interactions. METHODS: In this article, we introduce CatbNet, a multi network analyzer application which is prepared for network comparison objectives. RESULT AND CONCLUSION: CatbNet uses many topological features of networks to compare their structure and foundations. One of the most prominent properties of this application is classified network analysis in which groups of networks are compared with each other.